Synergy of blood grouping and body sweating - Muhammad Imran Qadir; Muhammad Asad (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2019)
Objective of the present study was to correlate blood grouping with "sweating in body". ABO typing is the test to determine your blood group. In this test, you had to mix your blood with antibodies which were against the type of blood A and blood B. Blood typing is very important during pregnancy. When you had done the blood typing you have to see either Rh factor is present on the surface of your red blood cells or not. People with type A have anti B antibodies. And same in case of type B they have anti A antibodies. And there is a case of type O in which both type of antibodies i.e. A and B takes place. Total of 182 subjects participated in this study. The subjects were the students of Bahauddin Zakariya University Multan, Pakistan. ABO typing is the test to determine your blood group. In this test, you have to mix your blood with antibodies which are against the blood type A and blood type B. After this sample is check in sense that either blood cell is stick together or not. We took blood samples from 182 different subjects from their consent. These subjects were the students of Bahauddin Zakariya University Multan, Pakistan. It was concluded from the current study that B+ had maximum body sweating and AB- had minimum.